Differences and Interactions between Learning Outcomes, Learning Model, and Gender in Islamic Religious Education - Murharyana, Murharyana; Al Ayyubi, Ibnu Imam; Komarudin, Komarudin; Suryana, Irfan; Noerzanah, Firda; Rahmawati, Siti (Southeast Asian Journal of Islamic Education, 2024)
This study aimed to understand the view on differences and interactions between three essential aspects in Islamic religious education. They are students’ learning outcomes, the learning model, and student gender according to school origin. This study was conducted at SMPN 2 Parongpong, Al Amin Unggulan Junior High School, and Roudlotul ‘Ulum Junior High School. The total sample of this study was 123 students. Three learning models used were Problem-Based Learning (PBL), Contextual Teaching and Learning (CTL), and Conventional. This research used a quantitative approach and Analysis of Variance (ANOVA) tests for data analysis. This research instrument used a summative test, which has been tested for validity and reliability. The data analysis requirements consisted of a normality test using Kolmogorov-Smirnov and Shapiro-Wilk assisted by SPSS version 26 software. The research results show that there is a difference in students’ learning outcomes on the learning model according to the student’s school origin. Then, there is no difference in learning outcomes between male and female students according to school origin, and there is no significant interaction between the learning model for male and female students in determining the learning outcomes of Islamic religious education according to students’ origin school. Differences in learning outcomes occurred in the application of CTL learning models with Conventional and PBL with Conventional, while learning models of PBL and CTL do not differ significantly. This study highlights the importance of applying active learning models to achieve optimal learning outcomes.